National inception workshop: Philippines: Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2017)
The International Food Policy Research Institure (IFPRI) and the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA), in partnership with the Department of Agriculture (DA) and the Department of Trade and Industry (DTI), concluded the final leg in a series of five inception workshops under the Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns (ATMI-ASEAN) Programme on 10-11 August 2017 at the SEARCA Headquarters in Los Baños, Laguna, Philippines. The two-day inception workshop focused on developing the Philippine Action Plan toward achieving the programme’s target outcomes. Country-level inception workshops have been conducted in Cambodia, Lao PDR, Myanmar, and Vietnam. The workshop aimed for participants to 1) Gain good understanding of structural transformation and market integration as these relate to agricultural growth and food security in the Philippines; (2) Level-off on what the project hopes to achieve and on the roles of various stakeholders; (3) Identify promising commodities for regional and global value chains; and (4) Develop a Country Action Plan towards the achievement of the Programme’ target outcome, i.e., enhanced capacity of ASEAN member-states (AMS) to identify and design national strategies, policies, programs and national agri-food value chain investment initiatives that benefit small-scale rural producers (SSRPs).